Development and Maintenance of Parthenocarpic Gynoecious Cucumber (Cucumis sativus L.) via the Induction of Male Flowers through Different Chemicals (Plant Bulletin, 2025)
The induction of male flowers in gynoecious cucumber (Cucumis sativus L.) has become an important topic for increasing fruit set and crop yield. C. sativus has female flowers on its plant, which creates a hindrance in its breeding. Flowering in plants is a complex process influenced by morphological and physiological changes regulated by both internal and external factors. Gynoecious cucumbers produce fruits without fertilization and yield a higher crop. Efficient and environmentally sustainable methods to induce male flowers can contribute to optimizing resource utilization and reducing production costs. Sex manipulation is being done nowadays to achieve a balanced ratio of male and female flowers by the application of chemical agents. The purpose of this review was to maintain the cucumber genotypes that have high potential yield, good fruit set, good quality, and disease-resistant genotypes by using the silver nitrate, gibberellic acid, and silver thiosulfate to induce male flowers. AgNO3 showed best results at 400 and 600 ppm, and GA3 at 1500 and 2000 ppm in inducing the development of male flowers. Silver thiosulfate induced a favorable male flower ratio at concentrations of 200 mg/L and 250 mg/L. Plant hormones play a crucial role in sex expression, with ethylene and auxins promoting female flower development, while gibberellins stimulate male flower formation.Keywords: Gibberellic acid, seedless cucumber, sex expression, silver nitrate, silver thiosulphate
Keywords: Gibberellic acid; Seedless cucumber; seedless cucumber; Sex expression; Silver nitrate; Silver thiosulphate